Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1289/ehp.01109s5699
|View full text |Cite
|
Sign up to set email alerts
|

The role of nutrient loading and eutrophication in estuarine ecology.

Abstract: Eutrophication is a process that can be defined as an increase in the rate of supply of organic matter (OM) to an ecosystem. We provide a general overview of the major features driving estuarine eutrophication and outline some of the consequences of that process. The main chemical constituent of OM is carbon (C), and therefore rates of eutrophication are expressed in units of C per area per unit time. OM occurs in both particulate and dissolved forms. Allochthonous OM originates outside the estuary, whereas au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(60 citation statements)
references
References 96 publications
0
57
0
Order By: Relevance
“…Primary productivity was also slightly higher at the bloom station compared with the annual average, although not statistically significant (Student's t-test, P-value = 0.12). Concentrations of accessory pigments were used to distinguish the presence of different phytoplankton groups (Pinckney et al, 2001;Peierls et al, 2003). Among the accessory pigments measured, peridinin and fucoxanthin were used as proxies of dinoflagellate and diatom relative abundances, respectively.…”
Section: Bloom Environmental Conditionsmentioning
confidence: 99%
“…Primary productivity was also slightly higher at the bloom station compared with the annual average, although not statistically significant (Student's t-test, P-value = 0.12). Concentrations of accessory pigments were used to distinguish the presence of different phytoplankton groups (Pinckney et al, 2001;Peierls et al, 2003). Among the accessory pigments measured, peridinin and fucoxanthin were used as proxies of dinoflagellate and diatom relative abundances, respectively.…”
Section: Bloom Environmental Conditionsmentioning
confidence: 99%
“…In order to achieve sustainable development, mariculture farms have moved from near-shore to off-coastal regions in recent years [30]. Mariculture in offcoastal regions is thought to have less negative environmental impacts because the strong currents reduce the environmental pollution accumulation in the regions and also benefit culture [31]. Recent molecular analyses indicated that fish farming in coastal shallow water has a greater impact on sediment bacteria than that in open water and potentially enrich both fish and human pathogens in Baltic Sea sediment [32].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of these include global, estuarine, and coastal marine nitrogen cycling Herbert, 1999;Pinckney et al, 2001;Rabalais, 2002;Ryther and Dunstan, 1971;Vitousek et al, 1997), fate modelling in soils, groundwater, and surface freshwater systems Seitzinger et al, 2010Seitzinger et al, , 2005Van Drecht et al, 2003;Wollheim et al, 2008), atmospheric emissions and deposition (Lee et al, 1997;Roy et al, 2012;van Vuuren et al, 2011), emissions from agriculture (Beusen et al, 2008;Bouwman et al, 2009Bouwman et al, , 2002Butterbach-Bahl and Dannenmann, 2011;Carpenter et al, 1998), emissions from wastewater (Van Drecht et al, 2009, loadings from rivers Kroeze et al, 2012;Seitzinger et al, 2010), or impacts from excess nitrogen inputs and eutrophication to marine ecosystems (Cloern, 2001;de Jonge et al, 2002;Kitsiou and Karydis, 2011;Rabalais et al, 2009;Smith et al, 2006.…”
Section: S12 Complementary Information On Modelling Anthropogenic Smentioning
confidence: 99%